2017
DOI: 10.1093/gbe/evw301
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analyses and Prediction of Human Drug Side Effect Associated Proteins from the Perspective of Protein Evolution

Abstract: Identification of various factors involved in adverse drug reactions in target proteins to develop therapeutic drugs with minimal/no side effect is very important. In this context, we have performed a comparative evolutionary rate analyses between the genes exhibiting drug side-effect(s) (SET) and genes showing no side effect (NSET) with an aim to increase the prediction accuracy of SET/NSET proteins using evolutionary rate determinants. We found that SET proteins are more conserved than the NSET proteins. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…Indeed, we see that this is a strong correlation within our dataset (Supplementary Figure 1); e.g., drugs with blood-related indications are nearly ten times more likely to have targets with Mendelian genetic syndromes involving blood. Other confounders include variables that have been previously linked to side effects: properties of the protein such as its cross-tissue expression pattern 15 , properties of the gene such as evolutionary constraint 37 and corresponding intolerance of population genetic variation 27 , or properties of the drug such as modality or delivery route. To explore the relationship of genetics and side effects with these potential confounders, we gathered additional drug and gene information and built a dataset for regression modeling, to predict side effects in each organ system as dependent variables.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we see that this is a strong correlation within our dataset (Supplementary Figure 1); e.g., drugs with blood-related indications are nearly ten times more likely to have targets with Mendelian genetic syndromes involving blood. Other confounders include variables that have been previously linked to side effects: properties of the protein such as its cross-tissue expression pattern 15 , properties of the gene such as evolutionary constraint 37 and corresponding intolerance of population genetic variation 27 , or properties of the drug such as modality or delivery route. To explore the relationship of genetics and side effects with these potential confounders, we gathered additional drug and gene information and built a dataset for regression modeling, to predict side effects in each organ system as dependent variables.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that viruses may hijack these EGEPs, leading to severe or lethal symptoms. Drugs that directly target them may cause serious side effects or specific toxicity [ 35 ]. Therefore, we examined the enrichment of EGEPs in known drug targets and VTHPs of the 35 viruses.…”
Section: Resultsmentioning
confidence: 99%
“…A cutoff of the upper bound of the OE confidence interval <0.35 was used as suggested by Karczewski et al ( 31 ). Constraint was examined because previous studies have shown it to be predictive of genes exhibiting drug side effects ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…We defined a genetic feature called “coloc2 phenotype,” which is a drug target gene with a GWA phenotype that is driven by gene expression regulation through colocalization. We selected this genetic feature because previous studies have shown GWA loci phenotypes to be predictive of genes exhibiting drug side effects ( 32 ).…”
Section: Methodsmentioning
confidence: 99%